2022
DOI: 10.3390/jcm11247540
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for COVID-19 in Inflammatory Bowel Disease: A National, ENEIDA-Based Case–Control Study (COVID-19-EII)

Abstract: (1) Scant information is available concerning the characteristics that may favour the acquisition of COVID-19 in patients with inflammatory bowel disease (IBD). Therefore, the aim of this study was to assess these differences between infected and noninfected patients with IBD. (2) This nationwide case–control study evaluated patients with inflammatory bowel disease with COVID-19 (cases) and without COVID-19 (controls) during the period March–July 2020 included in the ENEIDA of GETECCU. (3) A total of 496 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Initially, SARS-CoV-2 vaccines caused hesitancy in the IBD, mainly due to fear of poor response and safety concerns. IBD represents impaired immune function due to the disease and the therapies used to control this illness[ 60 ]. Jena et al [ 164 ] in a systematic review and meta-analysis, analyzed the response to complete vaccination in IBD patients.…”
Section: Liver Manifestations Associated With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, SARS-CoV-2 vaccines caused hesitancy in the IBD, mainly due to fear of poor response and safety concerns. IBD represents impaired immune function due to the disease and the therapies used to control this illness[ 60 ]. Jena et al [ 164 ] in a systematic review and meta-analysis, analyzed the response to complete vaccination in IBD patients.…”
Section: Liver Manifestations Associated With Covid-19mentioning
confidence: 99%
“…In IBD patients, as in the general population, age and comorbidities increase the risk of severe COVID-19 and disease-related mortality[ 45 , 59 ]. A prospective observational study that included 482 patients confirmed that age over 60 years was correlated with severe COVID-19 [odds ratio (OR) = 4.59, 95%CI: 1.3-15.9] and was an independent risk factor related to death (OR = 7.1, 95%CI: 1.8-27.4), as to have two or more comorbidities (OR = 3.9, 95%CI: 1.3-11.6)[ 60 ]. Wetwittayakhlang et al [ 61 ] examined a cohort of 3516 IBD patients, of whom 82 were diagnosed with COVID-19 infection, and they observed that age over 55 years was an independent risk factor for developing severe COVID-19.…”
Section: Introductionmentioning
confidence: 97%